Identification of host factors required for Ty1 transposition in yeast - Jin, Shiyi (2008)
Tyl is a retrotransposon with a life cycle similar to that of retroviruses. In this project we used the budding yeast Saccharomyces cerevisiae to identifyhost factors necessary for Tyl transposition. The nuclear pore complex (NPC) resides on the membrane of the nuclear envelope (NE) and acts as a gateway for macromolecular transportation between the cytoplasm and the nucleus. A major class of proteins, which is localized to discrete regions of the NPC, is called nucleoporins. In this study 15 mutant yeast strains each with a non-essential nucleoporin deletion were used to carry out the transposition assay.